Central venous access device (CVAD) complications in Haemophilia with inhibitors undergoing immune tolerance induction: Lessons from the international immune tolerance study. (14th July 2015) - Rodriguez, V.; Mancuso, M. E.; Warad, D.; Hay, C. R. M.; DiMichele, D. M.; Valentino, L.; Kenet, G.; Kulkarni, R.
<x xml:space="preserve">Abstract</x> Introduction Central venous access devices (CVADs) are frequently required as stable long‐lasting venous access in children with haemophilia, especially those requiring immune tolerance induction (ITI) for inhibitors. CVAD infection is one of the most frequently reported catheter‐related complications in this patient population. Aim Detailed review of CVAD complications from the International ITI (I‐ITI) study and analysis of potential risk factors for such complications. Methods Retrospective analysis of prospectively obtained data from the I‐ITI study primarily focused on CVAD‐related complications. Results A total of 115 children were recruited and 183 CVADs were placed in 99 subjects resulting in 121, 206 CVAD‐days observed on‐study. A total of 124 CVAD infections were reported in 41 of 99 (41%) subjects with an overall infection rate of 0.94 per 1000 CVAD‐days (interquartile ranges 0–1.7). A similar number of infections were observed in the two treatment arms (median: 2 and 3 in high dose and low dose respectively). Infections occurred more frequently in the presence of external catheters than with fully implanted catheters (P = 0.026). Infected patients were significantly younger at the time of CVAD insertion (median age: 22 vs. 25 months, P = 0.020). Patients with Gram‐positive infections were also significantly younger than those with Gram‐negative infections (median age: 17 vs. 25 months, P < 0.0001). Conclusion CVAD infection was the most common complication observed in children with severe haemophilia and inhibitors in the frame of the I‐ITI study. Younger age at CVAD insertion and external CVAD were associated with higher risk for infection. ITI outcome was unaffected by CVAD infections.